Students' Interest in Football Participation at the Elementary School Level - Muh. Iwan (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: This study aimed to investigate the level of students’ interest in soccer among students of elementary school Inpres BTN IKIP II, Rappocini District, Makassar City, and to identify the factors influencing their interest in participating in soccer activities. The study focused on examining students’ interest levels and the underlying motivational factors associated with soccer participation. Methodology: This study employed a quantitative descriptive survey design. The sample consisted of 21 students selected from Elementary School Inpres BTN IKIP II, Rappocini District, Makassar City. Data were collected using a structured questionnaire based on a Likert scale covering motivation and aspirations, attitudes toward teachers and lessons, family support, facilities, and mass media factors.  Main Findings: The findings revealed that students’ interest in soccer was categorized as high, with 72.14% of students demonstrating a high level of interest and only 27.86% showing a low level of interest. The study further indicated that students’ interest was influenced by several factors, including motivation and aspirations, attitudes toward teachers and learning activities, family support, availability of facilities, and exposure to mass media.  Novelty/Originality of this study: The novelty of this study lies in its comprehensive assessment of elementary school students’ interest in soccer through multiple influencing dimensions, including personal, educational, familial, environmental, and media-related factors. The study provides localized empirical evidence regarding sports interest among primary school students and contributes to understanding how motivational and environmental factors shape participation in soccer activities within elementary education settings.